ANALISIS PENYIMPANGAN PENGGUNAAN LAHAN BERDASARKAN RENCANA TATA RUANG WILAYAH KABUPATEN SUMEDANG - Reny Khaerani; Santun R.P. Sitorus; Omo Rusdiana (TATALOKA, 2018)
Spatial plan is the result of spatial planning which is done through the process and procedure of arranging and determining based on the prevailing laws and regulations. The phenomenon that often happens is the deviation of existing land use with spatial plan. Sumedang Regency is experiencing a fairly rapid development, so there is an increase in human resource activity that implicate the widespread space needs and consequently deviation of land use is very vulnerable. The purpose of this study to determine the extent of deviation of land use occurs as well as what factors affect the occurence of irregular use of land. The analysis used in this study using GIS approach, Principal Component Analysis and Multiple Regression Analysis. The result of analysis shows that there are 25 types of deviation of existing land use and the most dominant is deviation into wetland (18,364 ha), dryland field (8,405 ha) and widened land (7,741 ha). While the factors that influence the occurence of deviation of land use are population and settlement, availability of land, infrastructure and accessibility, and sosioeconomic condition of society